2018
DOI: 10.11607/jomi.5810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium Surfaces on the Osteogenic Differentiation of Human Adipose-Derived Stem Cells

Abstract: This study confirmed that human adipose-derived stem cells could be successfully grown in serum-free, xeno-free culture medium suitable for clinical use. Adipose-derived stem cells thus show potential utility for bone regeneration in association with titanium surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…Following the initial adhesion, which reached a peak for the HA-blasted and bland acid etching implants, a non-significant proliferative phase occurred for all but one implant, namely, the laser treated implants on day three and the double acid etching implants on day seven. This stands in contrast to previous studies on titanium discs [ 7 , 18 , 20 ], and it might be due to the low cell density or the whole-body surface via the presence of solubilized metallic ions with negative effects, which cause inflammation and cytotoxicity as their concentration rises [ 49 , 50 ].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Following the initial adhesion, which reached a peak for the HA-blasted and bland acid etching implants, a non-significant proliferative phase occurred for all but one implant, namely, the laser treated implants on day three and the double acid etching implants on day seven. This stands in contrast to previous studies on titanium discs [ 7 , 18 , 20 ], and it might be due to the low cell density or the whole-body surface via the presence of solubilized metallic ions with negative effects, which cause inflammation and cytotoxicity as their concentration rises [ 49 , 50 ].…”
Section: Discussioncontrasting
confidence: 64%
“…Implants are mainly classified into four types based on their surface roughness, as determined by the arithmetical mean of the roughness area (Sa), defined as rough (Sa > 2.0 µm), moderately rough (Sa between 1.0–2.0 µm), minimally rough (Sa between 0.5–1.0 µm), or smooth (Sa < 0.5 µm) [ 15 , 16 ]. Many studies employing stem cells in vivo and in vitro in order to understand the mechanism of osseointegration [ 17 , 18 , 19 ] have found that implant titanium discs [ 20 , 21 ] with moderately rough surfaces enable better cell and bone connections than smoother or rougher surfaces [ 15 , 16 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Surface roughness is also linked to favorable effects on load transmission via the distribution of well-tolerated micro-strains, 0.25–0.50 µε [ 6 , 30 , 31 ], which also favor osteoblastic and progenitor cell differentiation [ 6 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The final desired outcome of all bone‐implanted biomaterial is the de novo bone formation connecting the implant to the host bone, termed osseointegration, and the majority of the efforts to develop and test new dental implant modifications rely on tests using osteoblasts or MSCs to predict the implant outcome (Bressel et al, 2017; Fu et al., 2009; Jiang et al., 2015; Lotz et al., 2017; Zanicotti et al., 2018). While these types of tests are important to understand the behavior of bone‐forming cells in response to biomaterial modifications, they ignore the contribution of the other cellular and biological processes that occur in the peri‐implant environment in the 14–21 days before bone formation begins that also affect osseointegration and ultimately dictate the fate of the implanted biomaterial (Biguetti et al., 2018; Vlahović et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One experiment has found that argon plasma modification on the surface of nanocomposite polyurethane scaffolds could have the same effect as before (Griffin et al, 2019). Other studies confirmed that Ti and TiO 2 surfaces have a positive effect on the osteogenesis of ASCs as well (Malec et al, 2016;Zanicotti et al, 2018;Cowden et al, 2019). It may help increase the osteogenic efficiency of ASCs and translate into clinical practice.…”
Section: Physical Stimulationmentioning
confidence: 98%